ANALISIS PERKEMBANGAN MORAL PESERTA DIDIK KELAS X SMA NEGERI 9 PONTIANAK - Putri Hartati; Purwanti Purwanti; Ana Fergina (Universitas Tanjungpura, 2021)
AbstractThis study aims to analyze the moral development of class X SMA Negeri 9 Pontianak. The method used is descriptive method with survey. The population study was 183 people with a sample of 35 students of class X SMA Negeri 9 Pontianak. The data technique use direct communication and indirect. Data aids using questionnaires and interviews. The results are in the moral development of class X students of SMA Negeri 9 Pontianak showing a fairly high category, namely the proportion of 72.46% according to the three existing aspects. The level of pre-conventional moral development in the category of